The Impact of Decision Support Systems on Smart City Management: A Field Study on a Sample of Leaders of the Jeddah Governorate Municipality - AlQurashi , Suzan; Al-Zahrani, Sarah (The Arab Journal of Administration, 2023)
The research aims to identify the impact of the dimensions of decision support systems (physical capabilities, human capabilities, technical capabilities, and organizational capabilities) on smart city management and learn about the level of services provided by smart cities. Also, determine the statistically significant differences between the averages of the study sample response according to the variables (gender - academic qualification - job title - age - number of years of experience). The study recommends several recommendations, the most important of which is urging leaders to continue providing and updating appropriate programs to efficiently, quickly, and accurately complete the work. Also, the study recommends that leaders should set up a system for training and recruiting human cadres. So, that will lead employees to enjoy a high degree of perfection, increase interest in workers’ participation in developing visions and plans in managing smart cities, and listening to their proposals, initiatives, and ideas in solving problems. Leaders urged attention to the flexibility of the smart city organizational structure in response to the changes that may occur to the surrounding environment. Besides, they have to consider working to include more Saudi cities within the scope of smart cities in the Arab world and the world.